Multiple, Unilateral Lisch Nodules in the Absence of Other Manifestations of Neurofibromatosis Type 1 - E. G. Adams; K. M. A. Stewart; O. A. Borges; T. Darling (Case Reports in Ophthalmological Medicine)
Lisch nodules associated with Neurofibromatosis Type 1 (NF1) are usually multiple and bilateral in nature. Here, we report a 21-year-old healthy, Caucasian female who was diagnosed with multiple, unilateral Lisch nodules during routine eye examination. A thorough history and physical examination revealed no other signs of NF1. We diagnosed the rare occurrence of numerous, unilateral Lisch nodules in the absence of additional features of NF1 in our patient and provide a discussion concerning the differential diagnosis of Lisch nodules as well as the potential genetic explanation of this finding.